Genesis of the formation of the cultural and social core of Odessa - Nadia Yeksarova; Vladimir Yeksarov (Vitruvio: International Journal of Architectural Technology and Sustainability)
The architectural and spatial environment of the city is an important part of the cultural heritage, a carrier of information about its formation. The life cycle of a diverse architectural environment forms a series of stages - from the concept-creation-realization-alterations-degradation and, finally, partial or complete loss. The main idea, the scenario of modeling the environment-phenomenon of Odessa was in the priority development of culture. The construction of the first City Theater in 1809 on the plateau of the coastal zone determined the formation of a system of rhythmically iridescent spaces of a social center. An analog of the ancient forum - “Odessa Acropolis or Odessa Agora” - was created at the intersection of Lanzheronovskaya and Rishelevskaya (Decumanus and Cardin) streets in full accordance with the recommendations of Vitruvius. After the theater was destroyed by fire in 1872, the project of the new theater was developed by the Viennese architects F. Fellner and H. Helmer. The size of the new Opera and Ballet Theater for 1,728 seats significantly exceeded the volume of the former, and the main planning axis of the theater was changed by 90 degrees (1884–1887). This actually became an act of destruction and the loss of the original intention of the script by architect G. Toricelli on the formation of the solemn “Road of Processions”. Elements of the architectural environment of the cultural center gradually adapted to the new changes. The process of the evolution of the environment often creates more contradictions and problems than it solves. The problem lies not only in avoiding alterations and losses but in how to preserve the value-psychological core of culture.